4
$\begingroup$

Could anyone help me to solve two equations with complex numbers? I would like to know if there is a way to solve them avoiding the usual substitution $z=a+ib$ because calculations are not very easy

$1)$$z^3\bar{z}+3z^2-4=0$

I tried in this way

$z^2(z\bar{z}+3)=4$

$z^2(|z^2|+3)=4$

But I'm stuck at this point

$2)$$ \begin{cases} |z^2+1|=1 \\ 2Re(z)=|z^2| \end{cases}$

Here I tried to substitute $\omega=z^2$ but it doesn't work

Thanks a lot in advice

$\endgroup$
1
$\begingroup$

1) Your equation $z^2(z\bar{z}+3)=4$ brings us close to the end. Let $|z^2|=c$, and take the norm of both sides. Then $c(c+3)=4$, giving $c=1$.

2) This one is a little messier. There is the obvious solution $z=0$. We look for non-zero solutions. Expanding the first equation tells us that $$z^2\bar{z}^2+(z^2+\bar{z}^2)=0.$$ From the second equation, $z^2\bar{z}^2=4(\text{Re}(z))^2$. Letting $z=re^{i\theta}$ and cancelling the $r$ we get $$4\cos^2\theta+2\cos(2\theta)=0.$$ The rest is straightforward. Use $\cos(2\theta)=2\cos^2\theta-1$.

$\endgroup$
  • $\begingroup$ Thanks! But why did you substitute also $z^2$ with $c$ ? Is in this case $|z^2(|z^2|+3)|=|z^2|(|z^2|+3)$ ? $\endgroup$ – Gianolepo Nov 21 '15 at 16:54
  • 1
    $\begingroup$ Yes, the norm of a product is the product of the norms. $\endgroup$ – André Nicolas Nov 21 '15 at 16:58
  • 1
    $\begingroup$ So we end up with the equation $z^2=1$. Not hard! $\endgroup$ – André Nicolas Nov 21 '15 at 17:15
  • 1
    $\begingroup$ @FrancescoCaruso: I may be repeating a mistake, but it still cancels, giving $\cos\theta=\pm \frac{1}{2}$. But the second equation forces positive, and forces norm equal to $1$. So we get the two non-real cube roots of unity. Now in case you are concerned, substitute in the first equation. They work. $\endgroup$ – André Nicolas Nov 23 '15 at 16:55
  • 1
    $\begingroup$ Oh, I see what your problem is, you are looking at the wrong equation. It is from $4(\text{Re}(z))^2+z^2+\bar{z}^2=0$ that I get the cancellation of $r^2$, and then trig equation. $\endgroup$ – André Nicolas Nov 23 '15 at 17:24
1
$\begingroup$

Actually, what you have done is pretty clever/lucky in that you know $(|z^2| + 3)$ is real so $z^2(|z^2| + 3) = 4$ means $z^2$ is real. So $z^2 = \pm |z^2|$. Set $w = z^2$ and you have either:

$w \ge 0; w^2 + 3w - 4 = 0 \implies (x + 4)(x - 1) \implies w = 1 \implies z = \pm 1$

$w < 0; w^2 - 3w - 4 = 0 \implies (x - 4)(x + 1) \implies w = -1 \implies z = \pm i$

So $z = \pm i, \pm 1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.